Development of artificial intelligence-based teaching factory in vocational high schools in Central Java Province - Wahjusaputri, Sintha; Nastiti, Tashia Indah; Bunyamin, Bunyamin; Sukmawati, Wati (Journal of Education and Learning (EduLearn), 2024)
The objective of this study is to examine and assess the progress of utilizing artificial intelligence (AI) in teaching factory learning to enhance the digital skills of vocational high school (SMK) students in the province of Central Java. This study employed a qualitative approach utilizing metaethnography, as well as a quantitative approach employing Aiken’s V formula and strength, weakness, opportunity, threat (SWOT) analysis to identify and analyze the issues that arise. The present study examines the locations of SMKN 2 Purbalingga and SMKS Telkom in Central Java. Furthermore, relevant documentation was also utilized as a source of data. The research findings indicate that the implementation of AI in teaching manufacturing learning has effectively facilitated the development of an online learning management system. This system is characterized by its organized and integrated approach inside the online learning management system. The administration of teaching materials may be conducted autonomously and facilitated by the utilization of diverse information and communication technology or e-learning functionalities, including chat, email, blogs, and social media platforms. The creation of new enterprises within the domain of AI. It is imperative for educational institutions to align their policies with the demands and requirements of the business.